2022
DOI: 10.3390/ijerph19053000
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of Nursing Care in Patients with Coronary Artery Disease: A Systematic Review

Abstract: Coronary artery disease is the leading cause of death worldwide and patient continuity of care is essential. Health professionals can help in the transition stage by providing resources to achieve pharmacological treatment adherence, as well as social and emotional support. The objective was to analyse the effects of nursing interventions based on continuity of care in patients with coronary artery disease after hospital discharge. A systematic review of randomised controlled trials and quasi-experimental stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Even though patients are informed about guidelines and lifestyles after hospital discharge, some key ways, such as prompt medication reconciliation, medication safety, disease management, patient education, and patient-provider communication, can improve the patient's care transition, finally being associated with reduced rates of readmission, emergency department visits, and death [ 12 , 13 ]. Therefore, promoting continuity of nurse care is necessary after discharge, mainly focusing on the needs and resources of the patients via taking advantage of active participation in self-care [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though patients are informed about guidelines and lifestyles after hospital discharge, some key ways, such as prompt medication reconciliation, medication safety, disease management, patient education, and patient-provider communication, can improve the patient's care transition, finally being associated with reduced rates of readmission, emergency department visits, and death [ 12 , 13 ]. Therefore, promoting continuity of nurse care is necessary after discharge, mainly focusing on the needs and resources of the patients via taking advantage of active participation in self-care [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, standardized and standardized training is also carried out for the team members, so that they can master and understand the standardized care mode for patients with traumatic brain injury, and finally improve the management mode of the disease by nurses. ② Patient-family paired cognitive intervention is the premise and guarantee to ensure continuous post-hospital care for patients ( 16 ). Only a correct cognitive system can ensure that patients consciously practice correct and scientific behaviors, thereby reducing the incidence of adverse events, avoiding risk factors, and making them face the disease with a more peaceful mind.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions aiming to enhance continuity of care have also been found to facilitate self-care in patients hospitalized due to heart failure 29 and coronary artery diseases 50 , and in patients visiting the emergency department of a cardiac hospital 51 . A systematic review of patients hospitalized due to coronary artery diseases describes continuity of care interventions as providing the prerequisites for patients to improve their selfcare capacity and adhere to healthy lifestyle changes 50 . Studies have also found associations between continuity of care and patient-reported measures such as health-related quality of life 29,50,[52][53][54] , and perceived control 55 .…”
Section: Continuity Of Carementioning
confidence: 99%
“…A systematic review of patients hospitalized due to coronary artery diseases describes continuity of care interventions as providing the prerequisites for patients to improve their selfcare capacity and adhere to healthy lifestyle changes 50 . Studies have also found associations between continuity of care and patient-reported measures such as health-related quality of life 29,50,[52][53][54] , and perceived control 55 .…”
Section: Continuity Of Carementioning
confidence: 99%